The development of carbon-neutral supply chains – Investigation of stakeholders and influencing factors - Steiner, Benedikt; Münch, Christopher (Proceedings of the Annual International Purchasing & Supply Education & Research Association (IPSERA) Conference, 2023)
Globally operating companies (e.g., Coca-Cola, AstraZeneca, BMW Group, General Motors (GM), Nippon Steel, Maersk), as well as governments (e.g., EU - Green Deal, Californian government - Net Zero, German government), have announced their ambition to be carbon neutral by different time points, mostly before 2050. Developing carbon-neutral supply chains (CNSCs) is an important contributor to achieving carbon neutrality. According to CDP, on average, emissions from the supply chain are 11.4 times higher than emissions from a company's own operational activities. There appear to be multiple stakeholders, including policymakers, NGOs, competitors, technology providers, customers, logistics providers, and others, driving carbon neutrality in various ways, adding complexity to this sustainable transition. In addition, distinct influences appear to push companies into accounting for, managing and reducing their carbon emissions, investing in zero-carbon technologies and offering reduced-carbon products. However, influential stakeholders and effective drivers of CNSCs remain uncertain. Therefore, this study aims to identify influential stakeholders as well as key drivers. This study employed a mixed methods approach, including in-depth interviews and a systematic literature review. First, semi-structured interviews with experts were applied to validate and elaborate on the stakeholders involved in developing CNSCs. Secondly, the papers deriving from the systematic literature review were examined using content analysis to identify influential factors driving the development of CNSCs. Accordingly, additional drivers are elaborated through in-depth semi-structured interviews with experts and the analysis of non-academic literature. The contribution of this study to building theoretical knowledge in the academic field of sustainable supply chain management is manifold. First, stakeholder theory is elaborated by identifying influential stakeholders and particularities of CNSCs. Secondly, the key drivers for the development of CNSCs are identified illustrating potential prospects for the future of carbon neutrality. In addition, this review reveals emerging drivers of future CNSC trends and developments. Third, the findings of this study offer strategic guidance for practitioners seeking to reduce carbon emissions. Finally, this study lays the foundation for future research within the emerging academic field of CNSC management. <
Keywords: Carbon-neutral; Supply Chain Management; Sustainability; Stakeholder Theory